COMPARISON OF IMMEDIATE EFFECTS OF EXTRACORPOREAL SHOCKWAVE THERAPY AND CONVENTIONAL PHYSICAL THERAPY IN PATIENTS WITH CALCIFIC TENDINITIS OF THE SHOULDER ROTATOR CUFF - Manoleva, Maja; Nikolikj Dimitrova, Erieta; Koevska, Valentina; Mitrevska, Biljana; Gocevska Gjerakaroska, Marija; GJerakaroska Savevska, Cvetanka; Kalchovska Ivanovska, Biljana; Stojanoska Matjanoska, Lidija; Daniela Gechevska; Jugova, Teodora; Malinovska Nikolovska, Liljana (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2023)
Calcific tendinitis of the shoulder is a frequent disorder with an unknown etiology. It is usually treated with different physical therapy modalities where extracorporeal shockwave therapy comes as a new effective method. The aim of the study was to compare extracorporeal shockwave therapy and conventional physical therapy in the treatment of calcific tendinitis of the rotator cuff of the shoulder. The study is a prospective, monocentric clinical trial involving 40 patients with calcific tendinitis of the rotator cuff of the shoulder who were divided into two groups: group 1 (study group), 20 patients receiving extracorporeal shockwave therapy and performing shoulder exercises, and group 2 (control group), 20 patients who received conventional physical therapy with therapeutic ultrasound and diadynamic currents and performed shoulder exercises. Patients were evaluated with a Numerical Pain Scale and the range of motion in the shoulder joint was assessed. Clinical findings were evaluated before starting treatment and at the end of the treatment. All patients after the treatment showed statistically significantly better results in the Numerical Pain Scale and the shoulder range of motion. Extracorporeal shockwave therapy is a safe and non-invasive treatment that reduces pain and improves range of motion in the treatment of calcific tendinitis of the rotator cuff.
Keywords: calcifying tendinitis; shoulder; extracorporeal shockwave therapy